Jaringan Advokasi Transnasional (GAATW) dalam Penyelesaian Isu Migrasi Pekerja Perempuan dan Perdagangan Manusia di Asia Tenggara - Monica Vira Ajeng Kristanti (Universitas Airlangga, 2021)
Southeast Asia is one of the regions that has a fairly high rate of labor migration, both as a contributor and a recipient country. However, this is not equated with strict regulations and laws. Violations of the rights of migrant workers are common in several countries. Unfortunately, ASEAN as a regional regional organization has not been able to provide targeted advocacy. The Transnational Advocacy Network (TAN) is here to provide recommendations and advocacy to migrant workers across countries. In this article, the transnational advocacy network that will be studied further is the Global Alliance Against Trafficking in Women (GAATW) which has been actively advocating and providing policy recommendations to five countries in Southeast Asia, namely Indonesia, Singapore, Cambodia, the Philippines, and Thailand. The research method used in this study is a qualitative method using secondary data. In this study, we can see how GAATW cooperates with several migrant worker unions in these countries, either by conducting research, advocating for victims, or by publishing publications aimed at the public and the government.